Expression Patterns of the Wnt Pathway Inhibitors Dickkopf3 and Secreted Frizzled-Related Proteins 1 and 4 in Endometrial Endometrioid Adenocarcinoma: An NRG Oncology/Gynecologic Oncology Group Study. Issue 1 (January 2016) - Eskander, Ramez N.; Ali, Shamshad; Dellinger, Thanh; Lankes, Heather A.; Randall, Leslie M.; Ramirez, Nilsa C.; Monk, Bradley J.; Walker, Joan L.; Eisenhauer, Eric; Hoang, Bang H.
Abstract : Objective: The aim of the study was to determine the differential expression patterns of the wingless-type (Wnt) pathway inhibitors Dkk3 (Dickkopf 3), SFRP1 (secreted frizzled-related protein 1), and SFRP4 in normal müllerian tissue and endometrial endometrioid adenocarcinoma specimens. Methods: Messenger RNA (mRNA) and protein levels of the Wnt pathway inhibitors Dkk3, SFRP1, and SFRP4 were evaluated by real-time reverse transcription–polymerase chain reaction and Western blot analysis. A total of 87 human tissue specimens were obtained from 60 women who participated in Gynecologic Oncology Group protocol 210. Twenty-seven normal müllerian tissues, 32 early-stage, and 28 advanced-stage endometrial endometrioid cancer specimens were analyzed. Results: Median age for this cohort was 60 years, with median body mass index of 32 kg/m 2 . There was a difference in Dkk3 protein expression between normal müllerian tissues and primary endometrial endometrioid adenocarcinoma samples ( P = 0.05). There was down-regulation of Dkk3, SFRP1, and SFRP4 mRNA expression in patients with high-grade disease ( P = 0.08, 0.06, and 0.05, respectfully). Furthermore, a decrease in SFRP1 and SFPR4 mRNA expression was noted in patients with a diagnosis of locoregional and distant disease recurrence. Lastly, a trend toward decreased progression-free survival in patients with low Dkk3, SFRP1, and SFRP4 mRNA expression levels was noted. Conclusions: Wnt pathway inhibitor (Dkk3, sFRP1, and/or sFRP4) expression was down-regulated in patients with high-grade disease and was associated with locoregional and distant disease recurrence. Despite sample size (power) limitations, these results support previous preclinical studies and may suggest a therapeutic role for Wnt signaling in endometrial cancer.